Asymmetric Intimacies: Negotiating Inter-ethnic Friendship Between Migrants and Urban Hosts in Selected Javanese Cities - Fadhil Maliky Islah; Basti Tetteng; Kurniati Zainuddin; Faradillah Firdaus (Universitas Muhammadiyah Surakarta, 2025)
Domestic migration in Indonesia, particularly from regions outside Java to urban centers on the island, has created complex spaces of interethnic interaction where emotio m,nal closeness does not automatically develop despite increasingly frequent social contact. This study aims to explore how intimacy is experienced and ne-gotiated in interethnic friendships between migrants from outside Java and native Javanese hosts, and to ex-amine how hosts perceive and respond to these relational dynamics in everyday interactions. This study employed an exploratory qualitative approach. Data were collected through in-depth interviews with ten participants, consisting of five migrants from outside Java and five native Javanese hosts. To enhance analytic rigor, dialogical cross-verification was used as an interpretive strategy to refine themes and ensure coherence across participant accounts. The findings reveal that interethnic friendships are shaped by tensions between ingroup comfort and outgroup awkwardness, as well as between social stability and demands for cultural adaptation. While hosts often display verbal hospitality and polite, formal interactions, these practices rarely translate into emotional openness, placing greater relational initiative on migrants. As a result, intimacy tends to develop asymmetrically, being spatially inclusive yet relationally selective, particular-ly when expectations of personal closeness clash with norms of formality. Collective settings such as reli-gious and community-based activities, however, offer more reciprocal engagement and reduce cultural exclu-sivity. These findings highlight the importance of social structures that support sustained cross-group interaction, contributing to theoretical understandings of asymmetric intimacy and informing efforts to foster more inclusive interethnic relationships in domestic migration contexts in Indonesia.